2010
DOI: 10.1002/jcb.22536
|View full text |Cite
|
Sign up to set email alerts
|

FGF signalling as a mediator of lineage transitions—Evidence from embryonic stem cell differentiation

Abstract: The fibroblast growth factor (FGF) signalling pathway is one of the most ubiquitous in biology. It has diverse roles in development, differentiation and cancer. Embryonic stem (ES) cells are in vitro cell lines capable of differentiating into all the lineages of the conceptus. As such they have the capacity to differentiate into derivatives of all three germ layers and to some extent the extra-embryonic lineages as well. Given the prominent role of FGF signalling in early embryonic development, we explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 102 publications
(122 reference statements)
0
24
0
Order By: Relevance
“…Interestingly, up-regulated genes include a number of transcription factors and proteins such as Id3 that suppress ESC differentiation, and several repressors of FGF/ERK signaling (e.g. Dusp6, Spry4, Spry2, Spred3; Villegas et al, 2010; Ying et al, 2003). …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, up-regulated genes include a number of transcription factors and proteins such as Id3 that suppress ESC differentiation, and several repressors of FGF/ERK signaling (e.g. Dusp6, Spry4, Spry2, Spred3; Villegas et al, 2010; Ying et al, 2003). …”
Section: Resultsmentioning
confidence: 99%
“…3A), suggesting their role in early embryogenesis and development (42)(43)(44)(45). Earlier, we showed that increased expression of uPAR with IR treatment induces the angiogenic ability of medulloblastoma cells (7,44).…”
Section: Mol Cancer Ther; 13(5) May 2014mentioning
confidence: 88%
“…stimulation of transcription of the pluripotency genes) as well as in indirect manner (e.g. stimulating the feeder layer cells) [76,77].…”
Section: Signalling Mediated By Erk1/2mentioning
confidence: 99%